Selective determination of Cr(III) by modified carbon nanotube paste electrode: a potentiometric study. Issue 5 (6th January 2022) - Barati, Zahra; Masrournia, Mahboubeh; Es'haghi, Zarrin; Jahani, Moslem; Ebrahimi, Javad
Abstract: BACKGROUND: Potentiometric detections based on ion‐selective electrodes offer the advantages of simplicity, speed, and low cost over other electrochemical methods. In this work, the preparation of a novel carbon‐paste electrochemical sensor containing the synthesized N‐(1‐(4‐bromophenyl)‐3‐oxo‐3‐phenylpropyl)acetamide is described. Multi‐walled carbon nanotubes (MWCNTs) were incorporated into the electrode composition to promote electron transfer reactions. The modified carbon paste electrode was evaluated as a selective sensor for the detection of chromium (III). RESULTS: The prepared sensor showed nearly stable potentials in the pH range of 4.0–6.5, with a fast response time (<15 s). At the optimum conditions, the potentiometric method exhibited a linear response toward Cr(III) concentration in the range of 5.0 × 10 −7 to 1.0 × 10 −3 mol L −1 with a Nernstian slope of 19.5 ± 0.1 mV per decade and a detection limit of 3.1 × 10 −7 mol L −1 . CONCLUSION: The proposed sensor possesses the advantages of good selectivity to Cr(III) and an improved detection limit compared to the results of some other studies. Better selectivity can be attributed to the ability of the ionophore to form a stable chelate with Cr(III) ions. The new Cr(III) sensor showed excellent stability over 8 weeks and its response time was comparable to other previously reported chromium ion‐selective electrodes (ISEs) . The simple, fast, and cheap synthesis method of ionophore provided other advantages for this study. The modified electrode was also used as a sensor for the end‐point detection in the potentiometric titration of Cr(III) against ethylenediaminetetra acetic acid (EDTA). © 2021 Society of Chemical Industry (SCI).